2018
DOI: 10.1016/j.bja.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous infusion of lidocaine significantly reduces propofol dose for colonoscopy: a randomised placebo-controlled study

Abstract: Background: Propofol use during sedation for colonoscopy can result in cardiopulmonary complications. Intravenous lidocaine can alleviate visceral pain and decrease propofol requirements during surgery. We tested the hypothesis that i.v. lidocaine reduces propofol requirements during colonoscopy and improves post-colonoscopy recovery. Methods: Forty patients undergoing colonoscopy were included in this randomised placebo-controlled study. After titration of propofol to produce unconsciousness, patients were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 32 publications
5
85
3
1
Order By: Relevance
“…These results are in agreement with those obtained by Forster and colleagues. 15 We found that, during colonoscopy, the intraoperative HR and SBP in group L were lower than those in group N. This difference can be explained (at least in part) by the analgesic effect provided by lidocaine. Bradycardia and hypotension are common adverse reactions of propofol.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…These results are in agreement with those obtained by Forster and colleagues. 15 We found that, during colonoscopy, the intraoperative HR and SBP in group L were lower than those in group N. This difference can be explained (at least in part) by the analgesic effect provided by lidocaine. Bradycardia and hypotension are common adverse reactions of propofol.…”
Section: Discussionmentioning
confidence: 59%
“…However, other studies have shown that IV lidocaine in non-obese patients could result in a remarked reduction of propofol during colonoscopy. 15,50 There are no lidocaine-related adverse reactions in patients undergoing bariatric surgery. 49 However, we will further explore the efficacy of intravenous lidocaine in non-obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine reduced propofol requirements, and improved postcolonoscopy pain and fatigue. (12) The effect of lidocaine on opioid consumption during PSA has not…”
Section: Discussionmentioning
confidence: 99%
“…(10,11) One study showed that lidocaine reduces the use of propofol during colonoscopy, though did not evaluate opioid administration. (12) Based on these studies, lidocaine could be a promising additional analgesic in IBD patients to minimise side effects on PSA.…”
Section: Introductionmentioning
confidence: 99%